Sosialisasi Website “Be Safe” untuk Pengaduan Kasus Bullying pada Remaja di SMP - Yessi Azwar; Donny Hendra; Maswir Maswir; Cindy Febriyeni; Siti Zakiah Zulfa; Yunni Safitri; Noviyanti Noviyanti (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Bullying is a persistent social issue frequently found in school settings and remains a concern in many countries. This study was initiated based on observations at SMPN 17 Pekanbaru, where numerous students were found to have experienced bullying. The purpose of this community service program was to introduce and promote a digital reporting platform for junior high school students, designed to be safe, interactive, and evidence-based, thereby enabling victims or witnesses to report incidents more easily. The methods applied included socialization, practical demonstration, and evaluation, involving 40 students as participants in the program. The intervention introduced the “BeSafe” website, which aims to provide a secure and user-friendly channel for reporting bullying anonymously and independently. The findings indicate that the website achieved a usability score of 82.2%, categorizing it as highly feasible and appropriate for use among adolescents. Furthermore, BeSafe was able to offer comfort, security, and accessibility for students in addressing bullying cases. An evaluation carried out one month after the program revealed that 20 bullying complaints had been successfully submitted through the platform, showing its effectiveness in encouraging students to speak up and utilize digital solutions without fear of exposure. In conclusion, the BeSafe platform is proven to be suitable as a medium for reporting bullying cases and holds significant potential to support preventive measures in schools. Beyond serving as a reporting tool, it can also act as an educational and protective medium that fosters a safer, more inclusive, and supportive school environment, ultimately contributing to the broader efforts of reducing bullying and enhancing students’ psychological well-being.